SISTEM REKAYASA BALIK SINYAL ELEKTROKARDIOGRAM (EKG) REVERSE ENGINEERING SYSTEM of ELECTROCARDIOGRAM (ECG) SIGNAL - , DIMAS AGIL ROESENO K ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A reverse engineering system software of Electrocardiogram signal that can perform ECG signal graph visualization and perform heartbeat sound simulation based on CSV (Comma Separated Value) format ECG record has created. These application utilize a database from PhysioNet site that provides an ECG records. The heart record that consisting of amplitude rows with specific intervals has processed by the application so EKG waveform can be plotted and converted into lub-dub heartbeat sound through WAVPLAY instruction by entering wave amplification and sampe rate input of heart record. System will calculating ECG waveform frequencies within certain period using R wave calculation. This software that was created using MATLAB is expected to be used as a learning tool for users to analyze an ECG signal graph and train users to listening the heartbeat rhythm. Based on test results of 70 samples on existing data in Apnea-ECG Database, this software can do ECG signal visualization that led to the medical diagnosis in the form of 34 samples in the category normal waves, 21 waves with interference, and 15 waves with noise. Based on 55 samples tests in heartbeat simulation, the diagnosis shows 44 samples is a normal heart rhythm sound and 11 other samples having murmur sound inside that indicating an heartbeat anomaly.